Peningkatan Hasil Belajar IPA Melalui Model Pembelajaran Problem Bassed Learning (PBL) Pada Siswa Kelas 4 SD Negeri 66 Ambon - Salenussa, Crisya; Rumahlatu, Dominggus; Pelamonia, Johannes (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
This study aims to describe the improvement of Natural Science (IPA) learning outcomes through the application of the Problem Based Learning (PBL) learning model in fourth-grade students of SD Negeri 66 Ambon. The study used a quantitative descriptive approach with 25 students as subjects. The research instruments consisted of tests and non-tests. The test instruments included a pretest to determine students' initial abilities and a posttest to measure improvements in learning outcomes, with a total of 14 questions (10 multiple choice and 4 essay). The non-test instruments were in the form of affective and psychomotor observation sheets and LKPD to assess attitudes, skills, and mastery of the material during the learning process. Data collection techniques were carried out through tests (pretest and posttest) and non-tests. Data analysis used a comparison of the obtained scores and total scores. The final score was obtained from a combination of process assessments and formative test results with the following composition: 20% LKPD, 20% affective aspects, 20% psychomotor, and 40% formative tests. Students are considered to have completed the course if they obtain a score of ? 70, and not yet completed if the score is 70. The results of the study indicate that students' initial abilities are in the not yet completed category (100%). After implementing the PBL model, there was an increase in learning outcomes in the cognitive, affective, and psychomotor aspects. The average formative test score reached 86.3 with all students achieving learning completion. Therefore, the application of the Problem Based Learning learning model has been proven effective in improving science learning outcomes for fourth-grade students at Public Elementary Schools.